ANALISIS PENERAPAN DAN PERLAKUAN AKUNTANSI MURABAHAH UNTUK PEMBIAYAAN KONSUMTIF - Ika Rahmadani (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2017)
AbstractThis  study  aims  to  know the  implementation  of  murabahah  financing  in  PT.  BankMuamalat Indonesia branch office Banda Aceh, such as the rule of murabahah financing,the procedure of murabahah financing, and accounting of Murabahah financing and the conformity of its implementation to Statement of Financial Accounting Standards (PSAK) No. 102. The study conducted by using a descriptive method. Descriptive method is to conclude, interpret and clarify the data in accordance with the actual events. The type of data  used  are primary data  and  secondary data  that obtained  from interviews  with financing staff in PT Bank Muamalat Indonesia Branch Office Banda Aceh. The authors obtained  the  results  of  research  with  a  conclusion  that  the  practices  in  PT  Bank Muamalat Indonesia Branch Office Banda Aceh is compliance with the Statement of Financial Accounting Standards (PSAK) No. 102. Kata kunci: pembiayaan murabahah, akuntansi pembiayaan murabahah, pembiayaan konsumen, PSAK 102